A Single Dose Monoclonal Antibody (mAb) Immunoprophylaxis Strategy to Prevent RSV Disease in All Infants: Results of the First in Infant Study with MEDI8897. (4th October 2017) - Domachowske, Joseph B; Khan, Anis; Esser, Mark T; Jensen, Kathryn M; Takas, Therese; Villafana, Tonya; Dubovsky, Filip; Griffin, M Pamela
Abstract: Background: RSV is the most common cause of lower respiratory tract infection (LRTI) among infants making prevention of RSV disease a public health priority. A significant unmet need exists for RSV prevention in healthy infants. Our goal is to develop a mAb with an extended half-life ( t ½ ) capable of protecting infants for an entire RSV season by using a single intramuscular (IM) dose. This study was conducted to evaluate the safety profile, pharmacokinetics (PK), RSV neutralizing antibody titers, and anti-drug antibody (ADA) responses for MEDI8897 in healthy preterm infants born between 32 and 35 weeks gestational age. Methods: Infants were randomized 4:1 to receive a single IM injection of MEDI8897 10mg ( n = 8), 25mg ( n = 31), 50mg ( n = 32) or placebo ( n = 18) and followed for 360 days. Enrollment occurred during the 2, 015 RSV seasons in the US, South Africa, and Chile. Blood was collected at multiple timepoints. Infants who met criteria for a medically-attended (MA) LRTI had nasal swabs obtained for RSV testing by RT-PCR. Results: A total of 85/89 (95.5%) infants completed the study. Adverse events (AEs) were reported in 17/18 (94.4%) placebo and 66/71 (93.0%) MEDI8897 recipients. Five serious AEs (three LRTIs, two febrile seizures) were reported in three MEDI8897 recipients. No events were consistent with hypersensitivity reactions. The estimated MEDI8897 serum t ½ ranged from 62.5 to 72.9 days. On day 151, 87% of the infants who received the 50mg dose of MEDI8897 had serum concentrations above the target EC90 level of 6.8 µg/ml, and 93.3% showed a ≥3-fold rise from baseline in serum anti-RSV neutralizing antibody titers. ADA was detected in 28.2% of MEDI8897 recipients, but when present was not associated with any safety findings. ADA was detected at day 361 only in 26.5% of subjects. MA-LRTI was reported in 5 (7%) MEDI8897 recipients through 150 days after dosing. The one subject with an MA-LRTI caused by RSV had received a 10mg dose of MEDI8897. Conclusion: In healthy preterm infants, the safety profile of MEDI8897 was favorable. The extended t ½ of MEDI8897 with the corresponding increase in RSV neutralizing antibody levels was confirmed and supports protection from RSV disease during a typical 5-month season with a single 50mg IM dose. This study was sponsored by MedImmune. Disclosures: J. B. Domachowske, Medimmune: Investigator, Research grant; Regeneron: Investigator, Research grant; Pfizer: Investigator, Research grant; Glaxo Smith Kline: Investigator, Research grant; Novavax: Investigator, Research grant; Janssen: Investigator, Research grant; A. Khan, MedImmune: Employee and Shareholder, Salary and stock; M. T. Esser, MedImmune: Employee and Shareholder, Salary and stock; K. M. Jensen, MedImmune: Employee and Shareholder, Salary and stock; T. Takas, MedImmune: Employee and Shareholder, Salary and stock; T. Villafana, MedImmune: Employee and Shareholder, Salary and stock; F. Dubovsky, MedImmune: Employee and Shareholder, Salary and stock; M. P. Griffin, MedImmune: Employee and Shareholder, Salary and stock